2020
DOI: 10.31234/osf.io/9v4hr
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Syllable is a synchronization mechanism that makes human speech possible

Abstract: Speech is a highly skilled motor activity that shares a core problem with other motor skills: how to reduce the massive degrees of freedom (DOF) to the extent that the central nervous control and learning of complex motor movements become possible. It is hypothesized in this paper that a key solution to the DOF problem is to eliminate most of the temporal degrees of freedom by synchronizing concurrent movements, and that this is done in speech through the syllablea mechanism that synchronizes consonantal, voca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 145 publications
(233 reference statements)
2
20
1
Order By: Relevance
“…The results showed that a neural network classifier can detect categorical information in the acoustic signal around the same time for the onset C/CL and the nucleus vowel. Therefore, the results support the notion of synchronisation -that the start of the vowel is synchronised with the onset consonant [9], for both singleton and cluster onsets [2]. Most importantly, contrary to the prediction of the c-center hypothesis, the results do not show that the cluster onset precedes the vowel onset.…”
Section: Acoustic Evidence For Onset C/cl and V Synchronycontrasting
confidence: 45%
See 1 more Smart Citation
“…The results showed that a neural network classifier can detect categorical information in the acoustic signal around the same time for the onset C/CL and the nucleus vowel. Therefore, the results support the notion of synchronisation -that the start of the vowel is synchronised with the onset consonant [9], for both singleton and cluster onsets [2]. Most importantly, contrary to the prediction of the c-center hypothesis, the results do not show that the cluster onset precedes the vowel onset.…”
Section: Acoustic Evidence For Onset C/cl and V Synchronycontrasting
confidence: 45%
“…Evidence for co-production between syllable initial segments has been shown from the very early days of phonetic research, e.g., the observation of lip rounding at the beginning of /ku/ [4], tongue rising at the start of /bi/ [5], and simultaneous articulation between onset cluster [6] [7]. This has led to models that predict CV synchrony at the syllable onset, including the articulatory syllable model [2], the Task Dynamics (TD)/Articulatory Phonology (AP) frameworks [8] and the synchronisation model of the syllable [9]. The strongest claim among these models is that the co-onset happens between the vowel and the very first consonant in an onset cluster, and the syllable is the domain of coarticulation [2].…”
Section: Introductionmentioning
confidence: 99%
“…The alignment method used in the present study is based on the assumption that underlying pitch targets associated with a syllable is synchronized with the entire syllable rather than with only the syllable rhyme (Xu and Liu, 2006;Xu, 2020). Based on this assumption, while voice breaks may mask continuous F0 contours, they do not interrupt the underlying laryngeal movements that produce them.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the F0 contour of a syllable in English is a movement toward an underlying pitch target associated with lexical stress as well as other concurrent functions (Fry, 1958;Liu et al, 2013;Xu and Xu, 2005). It is further shown that such target approximation movement is synchronized with the syllable in English (Prom-on, Xu and Thipakorn, 2009;Xu and Prom-on, 2014;Xu and Xu, 2005), just like in Mandarin (Xu, 1998(Xu, , 1999, i.e., starting from the syllable onset and ending by syllable offset (Xu and Wang, 2001;Xu, 2020).…”
Section: Spectrogram Of Utterances Consisting Of Vowels and Consonantsmentioning
confidence: 99%
“…The other hypothesized aspect of the pitch production mechanism is the syllabic synchronization of target approximation movements. That is, laryngeal and supralaryngeal movements are synchronized with re spect to the syllable (Xu 2020;Liu 2006, 2012). This assumption is motivated not only by observations like those shown in figure 11.2, but also by findings that the motor system is able to coordinate multiple movements at a fast speed only through full synchrony (Kelso 1984;Kelso, Southard, and Goodman 1979;Mechsner et al 2001).…”
Section: Articulatory Mechanismsmentioning
confidence: 99%